Kista radikuler besar yang melibatkan dasar cavum nasalis - Silviana Farrah Diba; Lusi Epsilawati; Rike Kapriani (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2019)
Objectives: This case will present a radicular cyst and its expansion effect, seen from cone beam CT (CBCT) 3D radiograph. Case Report: A 32-year-old patient complained about discoloration of her upper anterior teeth and swollen gums. Periapical radiograph for preliminary examination revealed a large radiolucent area with well-defined cortical border in periapical 21. In coronal view, the lesion extends to 22 also causes the destruction of the nasal cavity floor and palatal cortical bone. Endodontic, cyst enucleation, and bone graft was performed to the patient. After endodontic treatment, CBCT examination was performed to determine the extent of cyst lesions. Conclusion: Large lesion needs an adequate radiographic technique to examine anatomical structure involvement. In large cysts, CBCT examination is matter to consider.